Сontemporary Approaches to the Exploration of Fear of Cancer Recurrence: a Review of Foreign Studies - Lysnyk, Kateryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
Every year the number of cancer survivals who have successfully overcome cancer increases. However, with remission often comes concern about a possible recurrence of the disease, which can significantly impair quality of life. The article considers the latest definition of fear of cancer recurrence, the factors of its clinical level and existing measurement methods. Also an attempt is made to generalize information about personal factors, that increase the fear of cancer recurrence in cancer survivals (such as age, gender, level of education, life history, etc.) and the affiliation of them to certain categories of the population. The influence of the peculiarities of the disease and the type of the received treatment, including personalized (genetic, immune and molecular therapy), on the change in the level of fear of cancer recurrence is also considered. According to the review of foreign sources, it is concluded that currently there are no convenient and reliable screening methods for determining the clinical level of fear of cancer recurrence, and existing questionnaires have different validity on certain scales and need linguistic and cultural adaptation. Fear of cancer recurrence is likely to be a serious problem among those who receiving personalized therapy. Age, gender and level of social adaptation also significantly affect to the level of fear of cancer recurrence, as well as belonging to certain categories of the population and the uniqueness of the life experience. Further research should identify the features of the fear of cancer recurrence in cancer survivors in Ukraine, and take into consider the identified factors in forming a support program by psycho-oncologists, since the fear of cancer recurrence significantly affects of cancer survivals the quality of life.